The effect of application of bovine amniotic membrane on osteoblasts, osteocytes, and collagen in the post-extraction alveolar bone socket of Sprague Dawley rats - Wibowo, Artdhea Regita; Octarina, Octarina; Munadziroh, Elly; Handharyani, Ekowati (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Tooth extraction can result in loss of alveolar bone. The application of biomaterials Bovine Amniotic Membrane (BAM) that containing growth factors and collagen is expected to play a role in socket preservation. This study aimed to observe the effect of BAM application on the growth of osteoblasts, osteocytes, and collagen in histological preparate of the alveolar bone socket of Sprague Dawley rats (SD). Methods: 16 male SD rats were used in this group. SD rats were extracted on the mandible central incisivus. Afterward, it was divided into two groups, specifically the control group (without treatment) and the treatment group (BAM application). After extraction, the treatment group was applied with BAM with a size of 1.5 mm x 10 mm in socket alveolar bone. On the 14th and 28th day, the rats were euthanized and the alveolar bone socket of mandibular tissue was taken and stained with Hematoxylin Eosin (HE) and Masson Trichrome (MT). Results: The results of all groups showed that the number of osteoblasts and collagen thickness was higher on day 14th compared to day 28th, while osteocytes continued to increase from day 14th to 28th. The thickness of collagen, osteoblasts, and osteocytes in groups with BAM application was higher than without application. Statistical results showed that there were significant differences between groups (p<0.05). Conclusion: The application of BAM can act as material preservation socket. This biomaterial can accelerate recovery by increasing collagen thickness, osteoblasts, and osteocytes.